Meigs syndrome: About an uncommon case report - Slaoui, Aziz; Lazhar, Hanaa; Amail, Noha; Zeraidi, Najia; Lakhdar, Amina; Kharbach, Aicha; Baydada, Aziz (Clinical Journal of Obstetrics and Gynecology, 2023)
Background: Ovarian fibroma is a very unusual epithelial tumor representing less than 1% of all ovarian tumors. It can be asymptomatic and discovered during surgery or be associated with a pleural effusion preferentially located on the right side and a more or less abundant free ascites in the framework of the so-called Meigs syndrome. The challenge of management then lies in distinguishing benign from malignant since clinically, radiologically, and biologically everything points towards malignant which requires radical surgical treatment. We report here the case of a 69-year-old postmenopausal patient with a clinical form of Meigs' syndrome that strongly suggested ovarian cancer. Case presentation: We hereby report here the case of a 69-year-old patient, menopausal, gravida 4 para 3 with 3 live children delivered vaginally and one miscarriage. She presented with ascites, hydrothorax, and a solid tumor of the ovary. Serum CA 125 and HE 4 levels were very high. ROMA score was highly suggestive of malignancy. A hysterectomy with adnexectomy was performed. It was only the histological evidence of ovarian fibroma and the rapid resolution of its effusions that confirmed Meigs syndrome. Conclusion: Meigs syndrome is an anatomical-clinical entity that associates a benign tumor of the ovary, ascites, and hydrothorax. Highly elevated CA 125 and HE-4 tumor markers often point clinicians toward a malignant tumor and compel radical surgical treatment. This case report reminds us once again that only histology confirms the diagnosis of cancer.